Effectiveness of Dipeptidyl Peptidase IV Inhibitors in the Management of Chronic Obstructive Pulmonary Disease: A Meta-Analysis - Davian, Joas Vinsensius; Zen Fadil Ahmad; Rouly Pola Pasaribu (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Chronic obstructive pulmonary disease (COPD) is a major global health issue. Recent research suggests dipeptidyl peptidase IV (DPP-IV) inhibitors, primarily used in diabetes management, may have beneficial effects on lung function and inflammation in COPD. This meta-analysis aims to assess the efficacy and safety of DPP-IV inhibitors in COPD. Methods: A systematic search of PubMed, Embase, and Cochrane Library databases was conducted from January 2018 to June 2024. Randomized controlled trials (RCTs) comparing DPP-IV inhibitors with placebo or standard COPD therapy in patients with COPD were included. Data on lung function (FEV1), quality of life, exacerbations, and adverse events were extracted. Meta-analyses were performed using random-effects models. Results: Ten RCTs involving 4,520 patients were included. DPP-IV inhibitors were associated with a significant improvement in FEV1 compared to placebo or standard therapy (mean difference: 55 ml, 95% CI: 30-80 ml, p<0.001). Quality of life scores also showed a trend toward improvement. The rate of moderate-to-severe exacerbations was significantly lower in the DPP-IV group (risk ratio: 0.75, 95% CI: 0.60-0.93, p=0.008). Adverse events were similar between groups. Conclusion: DPP-IV inhibitors may be a promising adjunctive therapy in COPD management, improving lung function, and quality of life, and reducing exacerbations. Further research is warranted to confirm these findings and investigate long-term effects.